State Anxiety Is Associated with Cardiovascular Reactivity in Young, Healthy African Americans - Mildred A. Pointer; Sadiqa Yancey; Ranim Abou-Chacra; Patricia Petrusi; Sandra J. Waters; Marilyn K. McClelland (International Journal of Hypertension)
Although several studies have shown that enhanced cardiovascular reactivity can predict hypertension development in African Americans, these findings have not been consistent among all studies examining reactivity and hypertension susceptibility. This inconsistency may be explained by the influence of anxiety (state and trait) on the blood pressure response to stress. Therefore, this study sought to determine whether anxiety is associated with blood pressure response to cold pressor (CP) and anger recall (AR) stress tests in young healthy African Americans. Modeling using state and trait anxiety revealed that state anxiety predicts systolic (SBP) and diastolic blood pressure DBP response to CP and AR (P≤0.02). Interestingly, state anxiety predicted heart rate changes only to CP (P<0.01; P=0.3 for AR). Although trait anxiety was associated with SBP response to AR and not CP, it was not a significant predictor of reactivity in our models. We conclude that anxiety levels may contribute to the variable blood pressure response to acute stressors and, therefore, should be assessed when performing cardiovascular reactivity measures.